Sentence Structures: A Case Study of Children's Spontaneous Speech - Suparwoto Sapto Wahono; Maftukhatur Rofiqotul Khilmiah; Khoirunnisa (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
Spontaneous speech offers insights into how children use and construct sentences in real communicative contexts. This study investigates sentence structures used by two Indonesian children aged 12 and 10 in natural conversations using Indonesian language. It aims to analyze syntactic patterns found in their spontaneous speech. This study was a case study used a qualitative approach. The data collection used digital document that the children were recorded during natural interactions at home, and the data were transcribed and analyzed according to syntactic complexity: simple, compound, complex, and compound-complex sentences. The findings show that the 10-year-old child mostly produced simple and compound structures, while the 12-year-old child demonstrated a broader range of complex and compound-complex structures. This suggests that syntactic development in children is closely tied to age and cognitive growth. The study contributes to understand sentence structure acquisition in Indonesian language and emphasizes the importance of spontaneous data in language development research.